Factors Affecting Exclusive Breastfeeding Practice using Social Cognitive Theory Constructs: A Multilevel Evidence from Madiun, East Java - Rezyana Budi Syahputri; Pawito Pawito; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Exclusive breastfeeding for infants up to 6 months of age is the most effective way to ensure the health and the viability of the child. Exclusive breastfeeding coverage still does not meet the target due to various factors. This study aimed to determine the effectiveness level of health promotion of exclusive breastfeeding program in the integrated health service in Madiun, East Java.Subjects and Method: This was an a cross-sectional study conducted in Madiun, East Java, from February to May 2020. A sample of 200 lactating mother who had infants aged 6 to 24 months was selected randomly. The dependent variable was exclusive breastfeeding practice. The independent variables were health promotion program, observational learning, role model, vicarious learning, imitation, attitude, outcome expectation, self regulation, self-efficacy, reinforcement, and integrated health post contextual. The data were collected using questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Exclusive breastfeeding practice increased with adequate health promotion program (OR= 3.08; 95% CI= 1.06 to 8.94; p= 0.038), high observational learning (OR= 3.86; 95% CI= 1.31 to 11.39; p= 0.014), strong role model (OR= 4.01; 95% CI= 1.12 to 14.29; p= 0.033), vicarious learning (OR= 4.46; 95% CI= 1.34 to 14.82; p= 0.015), strong imitation (OR= 2.74; 95% CI= 1.02 to 7.35; p= 0.045), positive attitude (OR= 3.51; 95% CI= 1.04 to 11.88; p= 0.043), positive outcome expectation (OR= 4.04; 95% CI= 1.32 to 12.38; p= 0.014), strong self-regulation (OR= 2.36; 95% CI= 0.93 to 5.99; p= 0.068), strong self-efficacy (OR= 5.35; 95% CI= 1.81 to 15.77; p= 0.002), and strong reinforcement (OR= 3.90; 95% CI= 1.21 to 12.57; p= 0.022). There was a contextual effect of integrated health post on exclusive breastfeeding practice with intraclass correlation (ICC)= 10.97%.Conclusion: Exclusive breastfeeding practice is affected by health promotion program, observational learning, role model, vicarious learning, imitation, attitude, outcome expectation, self regulation, self-efficacy, and reinforcement. Integrated health post has a contextual effect on exclusive breastfeeding practice.Keywords: exclusive breastfeeding, health promotion, social cognitive theory.Correspondence: Rezyana Budi Syahputri. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: rezyanabs@gmail.com. Mobile: +6282325750134.Journal of Health Promotion and Behavior (2020), 05(03): 169-173https://doi.org/10.26911/thejhpb.2020.05.03.03